Diversity and trade-offs of water values in the Akaki River system in Ethiopia: context of urban–rural linkage - Haileslassie, Amare; Tesema, Ephrem; Mersha, M.; Bekele, Tilaye Worku; Dessalegn, Mengistu; Haile, Alemseged Tamiru (Springer, 2024)
The objectives of the study were to investigate community perception and articulation of diverse and priority water values and examine water value trade-offs in the context of urban–rural interaction. The study applies the socio-ecological system framework and integrates bio-physical and socioeconomic methods into it. These methods include Household Surveys (HHs); Focused Group Discussions (FGD); Key Informant Interviews (KII); Cumulative Pollution Index (CPI); GIS for spatial analysis and literature review. Through HHs, 23 water values were identified in Akaki. Most respondents of the HHs prioritized three water values (water for agriculture, livestock, and domestic use). The stakeholder consultation substantiated the priority for domestic water value but also acknowledged waste assimilation services of rivers that absorb and strew pollutants from industries and households. The result of KII suggests that water system structures (e.g., reservoirs) are the mnemonic value for past events and sustain scenic values of local, national, and global importance. The Cumulative Pollution Index (CPI) based pollution assessment indicates that the Akaki water system lost a significant number of its water value (compared to the actual uses) due to river pollution across its reach and more critically at its outlet. The differences between the CPI value-based recommended water uses and actual water uses reflect a lack of options, awareness gaps, and a low level of policy enforcement. It is concluded that policy directions and decision-making need to acknowledge the multiple water values and competing uses of water, as points of departure, to reconcile water value trade-offs, conserve water and create awareness.